2022
DOI: 10.3389/fcimb.2022.849224
|View full text |Cite
|
Sign up to set email alerts
|

The Age-Driven Decline in Neutrophil Function Contributes to the Reduced Efficacy of the Pneumococcal Conjugate Vaccine in Old Hosts

Abstract: Despite the availability of vaccines, Streptococcus pneumoniae (pneumococcus) remains a serious cause of infections in the elderly. The efficacy of anti-pneumococcal vaccines declines with age. While age-driven changes in antibody responses are well defined, less is known about the role of innate immune cells such as polymorphonuclear leukocytes (PMNs) in the reduced vaccine protection seen in aging. Here we explored the role of PMNs in protection against S. pneumoniae in vaccinated hosts. We found that deplet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 54 publications
1
16
0
Order By: Relevance
“…To determine if mitochondrial ROS were important for the antimicrobial function of PMNs, we treated PMNs with MitoTEMPO and measured the ability of PMNs to kill S . pneumoniae TIGR4 strain using an established opsonophagocytic (OPH) killing assay [ 2 , 12 , 32 34 , 49 ]. We found that treatment with MitoTEMPO lead to a complete abrogation of bacterial killing by PMNs ( Fig 4A ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine if mitochondrial ROS were important for the antimicrobial function of PMNs, we treated PMNs with MitoTEMPO and measured the ability of PMNs to kill S . pneumoniae TIGR4 strain using an established opsonophagocytic (OPH) killing assay [ 2 , 12 , 32 34 , 49 ]. We found that treatment with MitoTEMPO lead to a complete abrogation of bacterial killing by PMNs ( Fig 4A ).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, infection of macrophages with S. aureus results in mitochondrial-derived vesicles containing anti-bacterial hydrogen peroxide that localize with bacterial containing phagosomes [16]. S. pneumoniae are extracellular bacteria that are killed very efficiently once engulfed by PMNs [34,49]. However, the dynamics of MitROS production by PMNs and their compartmentalization with the cell remain open questions and will be the focus of future studies in our laboratory.…”
Section: Plos Pathogensmentioning
confidence: 99%
“…We previously found that scavenging/ detoxifying ROS completely abrogates the ability of PMNs to kill S. pneumoniae [12]. To determine if mitochondrial ROS were important for the antimicrobial function of PMNs, we treated PMNs with MitoTEMPO and measured the ability of PMNs to kill S. pneumoniae TIGR4 strain using an established opsonophagocytic (OPH) killing assay [2, 12, 3234, 49]. We found that treatment with MitoTEMPO lead to a complete abrogation of bacterial killing by PMNs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study conducted in animal models has shown that the aging process impairs vaccine-mediated protection against S. pneumoniae due to the impaired ability of neutrophils to kill the bacteria, even when they were opsonized with immune sera from young controls [ 31 ]. In the increased incidence/development of cancer in older people, neutrophils appear to play an immunosuppressive role, interfering with the normal process of immune surveillance against cancer-associated antigens [ 32 ].…”
Section: Immunosenescence Of the Innate Immune Cellsmentioning
confidence: 99%